Analisis Pengaruh Biaya Perkuliahan, Biaya Promosi dan Faktor Eksternal (Uncontrollable) Terhadap Penerimaan Jumlah Mahasiswa Baru di Kampus STMIK Atma Luhur Pangkalpinang - Seno Hadi Saputro; Hengki Hengki (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2016)
This research is performed in order to test the influence of tuition, promotion costs and macro variable (uncontrolable) toward the number of new admissions. Methodology research as the sample used purposive sampling and this research in STMIK AtmaLuhur. Data analysis with multiplier regression of panel data common effect method. Empirical evidence of analysis show as tuition, promotion costs, inflation, kurs, BI Rate not influence toward the number of new amissions Strata 1 in STMIK AtmaLuhur. Inflation, Kurs, Bi Rate not influence toward the number of new admissions Diploma 3 while tuition have negative influence toward the number of new admissions and promotion costs have positive influence toward the number of new admissions Diploma 3 in STMIK Atma Luhur.